2009
DOI: 10.1152/ajplung.00007.2009
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced alveolar epithelial-mesenchymal transition requires mitochondrial ROS and hypoxia-inducible factor 1

Abstract: -Patients with acute lung injury develop hypoxia, which may lead to lung dysfunction and aberrant tissue repair. Recent studies have suggested that epithelial-mesenchymal transition (EMT) contributes to pulmonary fibrosis. We sought to determine whether hypoxia induces EMT in alveolar epithelial cells (AEC). We found that hypoxia induced the expression of ␣-smooth muscle actin (␣-SMA) and vimentin and decreased the expression of E-cadherin in transformed and primary human, rat, and mouse AEC, suggesting that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
175
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(202 citation statements)
references
References 54 publications
14
175
3
4
Order By: Relevance
“…Our present studies indicate that IL-17A is a potent inducer of EMT; in contrast, IL-17C and IL-17F fail to induce EMT in these cells. Here we observed that IL-17-mediated EMT is comparable in both normal primary human small airway epithelial and, using a well-documented EMT cell line, RLE-6TNs (20,39,50,54). These data provide more evidence demonstrating IL-17-mediated EMT similar to its effect in tumor-derived epithelial cells (36).…”
Section: L409 Il-17 Mediated Col(v) Overexpression and Emtsupporting
confidence: 62%
“…Our present studies indicate that IL-17A is a potent inducer of EMT; in contrast, IL-17C and IL-17F fail to induce EMT in these cells. Here we observed that IL-17-mediated EMT is comparable in both normal primary human small airway epithelial and, using a well-documented EMT cell line, RLE-6TNs (20,39,50,54). These data provide more evidence demonstrating IL-17-mediated EMT similar to its effect in tumor-derived epithelial cells (36).…”
Section: L409 Il-17 Mediated Col(v) Overexpression and Emtsupporting
confidence: 62%
“…Transforming growth factor‐β1 is a classical EMT‐promoting cytokine, and many studies have shown the relationship between HIF‐1α and TGF‐β1 in the process of EMT 13, 35, 36. We also found that TGF‐β1 has a positive correlation with HIF‐1α as well as Snail and β‐catenin in PQ poisoning‐induced pulmonary fibrosis, the latter of which are the two other EMT‐promoting cytokines in addition to TGF‐β1 26.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was suggested that the hypoxic signal can be triggered through HIF, resulting in the occurrence of EMT (34). Tumor growth factor-β was initially confirmed as an inducer of EMT in normal mammary epithelial cells and has since been shown to mediate the EMT in tumorigenesis (35,36). various transcription factors are involved in TGFβ signals, including ZEB1 and SNAIL (37).…”
Section: Discussionmentioning
confidence: 99%